Ag-catalyzed azide-alkyne cycloaddition: copper free approaches for synthesis of 1, 4-disubstituted 1, 2, 3-triazoles. Issue 1 (2nd January 2020) - Sultana, Jasmin; Sarma, Diganta
ABSTRACT: This review mainly focuses on purely Ag-catalyzed 1, 3-dipolar azide-alkyne cycloaddition (AgAAC) so called click reaction to synthesize 1, 4-regioisomers of 1, 2, 3-triazoles. The most established catalyst Cu (I) developed by Fokin–Sharpless and Meldal group in 2002 for AAC reaction have been further extended to different other transition metal catalysts because of certain limitations of CuAAC methods. Among different transition metal catalyzed methods, AgAAC is the most studied one having same electronic configuration, d 10 (AgI) with that of CuI and shows high catalytic performance.